Genkwanin Prevents Lipopolysaccharide-Induced Inflammatory Bone Destruction and Ovariectomy-Induced Bone Loss - Fu, Xin; Sun, Xiaochen; Zhang, Chenxi; Lv, Nanning; Guo, Huan; Xing, Chunlei; Lv, Juan; Wu, Jiwen; Zhu, Xiaoli; Liu, Mingming; Su, Li (Frontiers in Nutrition, 2022)
Objectives The first objective of this study was to probe the effects of genkwanin (GKA) on osteoclast. The second goal of this study was to study whether GKA can protect lipopolysaccharide (LPS) and ovariectomized (OVX) induced bone loss. Materials and Methods Various concentrations of GKA (1 and 10 mg/kg) were injected into mice. Different concentrations of GKA (1 and 5 μM) were used to detect the effects of GKA on osteoclast and osteoblast. Key Findings GKA attenuated the osteoclast differentiation promoted by RANKL and expression of marker genes containing c-fos, ctsk as well as bone resorption related gene Trap and to the suppression of MAPK signaling pathway. In addition, GKA induced BMMs cell apoptosis in vitro. Moreover, GKA prevented LPS-induced and ovariectomized-induced bone loss in mice. Conclusion Our research revealed that GKA had a potential to be an effective therapeutic agent for osteoclast-mediated osteoporosis.